2017
DOI: 10.1111/inr.12381
|View full text |Cite
|
Sign up to set email alerts
|

Risk factors of falls among inpatients with cancer

Abstract: The predictive factors for falls reflect the nature of the patient's environment, culture and disease. Falls have a negative effect on patient safety and can significantly influence quality of life. Policies for patient safety need more specialized and customized approaches.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 11 publications
(25 citation statements)
references
References 24 publications
(82 reference statements)
1
19
0
Order By: Relevance
“…Besides, patients experiencing fatigue likely have asthenia of lower limbs which may result in gait imbalance. These fall predictors were frequently found in most if not all of previous studies [3,6,7,[11][12][13][25][26][27][28].…”
Section: Discussionmentioning
confidence: 84%
See 4 more Smart Citations
“…Besides, patients experiencing fatigue likely have asthenia of lower limbs which may result in gait imbalance. These fall predictors were frequently found in most if not all of previous studies [3,6,7,[11][12][13][25][26][27][28].…”
Section: Discussionmentioning
confidence: 84%
“…In line with previous studies, we found for the most of the candidate fall predictors higher prevalences in the cases group as compared to controls. This was applies to the need for walking aid, having a neurologic disease, impaired vision/hearing, delirium, anxiety/depression, gate imbalance disorders, fatigue, hyposthenia of lower limbs, use of ambulatory devices, diuretics, hypnotics and opioids [3,[8][9][10][11]13]. Conversely, contrast with previous studies, we found no statistically signi cant differences in prevalences of having comorbidities such as cardiovascular, endocrine and respiratory diseases, treatment induced neuropathy, the presence of plegies, and the use of antihypertensive, hypoglicemic agents and having received blood products transfusions in the last 24 hours.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations